2010
DOI: 10.1074/jbc.m109.082883
|View full text |Cite
|
Sign up to set email alerts
|

Neurons Efficiently Repair Glutamate-induced Oxidative DNA Damage by a Process Involving CREB-mediated Up-regulation of Apurinic Endonuclease 1

Abstract: Glutamate, the major excitatory neurotransmitter in the brain, activates receptors coupled to membrane depolarization and Ca 2؉ influx that mediates functional responses of neurons including processes such as learning and memory. Here we show that reversible nuclear oxidative DNA damage occurs in cerebral cortical neurons in response to transient glutamate receptor activation using non-toxic physiological levels of glutamate. This DNA damage was prevented by intracellular Ca 2؉ chelation, the mitochondrial sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
83
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 63 publications
1
83
0
1
Order By: Relevance
“…[1][2][3][4] It is well documented that the interaction of ROS with lipids and proteins has a significant impact on cellular function in the brain. [5][6][7][8] However, recent investigations have revealed that DNA damage/repair can contribute to the age-associated neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] It is well documented that the interaction of ROS with lipids and proteins has a significant impact on cellular function in the brain. [5][6][7][8] However, recent investigations have revealed that DNA damage/repair can contribute to the age-associated neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] However, recent investigations have revealed that DNA damage/repair can contribute to the age-associated neurodegeneration. [2][3][4] Indeed, significant damage to DNA causes activation of pro-apoptotic and DNA repair proteins. Depending on the size of DNA damage and the success of repair, cells either die or survive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Vazquez-Martin and colleagues found that metformin leads to the phosphorylation and activation of the check point homologue kinase 2 (chk2), which mediates the response of the ATM pathway in response to DNA damage (26). In addition, they showed that metformin treatment enhanced the phosphorylation of cAMP-response element binding protein, an ATM kinase-regulated event in response to oxidative DNA damage (27). Because DDR is a major component of the innate tumor suppressor mechanism, activation of the ATM pathway could contribute to metformin's cancer preventive properties.…”
mentioning
confidence: 99%
“…On the other hand, activation of signaling cascades that modify activity of mitochondrial ETC activity is also a possibility for which there is precedence (Figure 1). For example, the activation of glutamate receptors in neurons has been reported to increase mitochondrial SO production by a mechanism involving Ca 2+ influx through ionotropic glutamate receptors in the plasma membrane [15].…”
mentioning
confidence: 99%